A case report of healthcare-associated psittacosis - Fei Deng; Qibin Lin; Xiaohong Xu; Changsong Li; Jianbo Xu; Hanxiang Nie (Journal of Infection in Developing Countries)
Introduction: Psittacosis is a well-recognized zoonotic infectious disorder caused by Chlamydia psittaci (C. psittaci). Human-to-human transmission of C. psittaci has rarely been reported previously, especially in the case of healthcare-associated infections.